Life beyond a jar: Effects of tank size and furnishings on the behaviour and welfare of Siamese fighting fish (Betta splendens) - Naomi Clark-Shen; Juliette Tariel-Adam; Anya Gajanur; Culum Brown (Animal Welfare)
Globally, Siamese fighting fish (Betta splendens) continue to be sold and kept in small, barren jars or tanks, with little concern for their welfare. This study aimed to examine the impact of housing size and furnishings (i.e. live plants, refuges) on the behaviour of Siamese fighting fish, to understand optimal tank conditions. Thirteen male Siamese fighting fish were rotated between five different housing conditions: ‘jar’ (1.5 L); ‘small’ (3.3 L); ‘medium’ (5.6 L); ‘large’ (19.3 L); and ‘large-barren’ (19.3 L). All tanks had gravel and furnishings, except the large-barren tank which was devoid of these. Overall, tank size influenced behaviour. Fish were significantly more active and spent significantly less time resting and performing ‘abnormal’ behaviours (hovering and stereotypic swimming), in the large tank compared to the smaller tanks. Tank furnishings also influenced behaviour. Fishes in the large-barren tank performed more ‘abnormal’ behaviours (hovering, stereotypic swimming, interaction with the walls), compared to the large tank which had furnishings. These results suggest that the small, barren jars and tanks that Siamese fighting fish are often housed in are detrimental to their welfare, and larger, furnished tanks are more optimal. Behavioural variations were observed between the fish in this study, highlighting individual fish personality. We recommend a minimum tank size of 5.6 L for the display and sale of Siamese fighting fish, and tanks larger than this for keeping Siamese fighting fish at home. All tanks should contain gravel, live plants and refuges.